2011
DOI: 10.1371/journal.pgen.1002097
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Regulatory Factor 8 Regulates Pathways for Antigen Presentation in Myeloid Cells and during Tuberculosis

Abstract: IRF8 (Interferon Regulatory Factor 8) plays an important role in defenses against intracellular pathogens, including several aspects of myeloid cells function. It is required for ontogeny and maturation of macrophages and dendritic cells, for activation of anti-microbial defenses, and for production of the Th1-polarizing cytokine interleukin-12 (IL-12) in response to interferon gamma (IFNγ) and protection against infection with Mycobacterium tuberculosis. The transcriptional programs and cellular pathways that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 62 publications
5
59
0
Order By: Relevance
“…Indeed, IRF8 directly binds to and upregulates multiple genes encoding major histocompatibility complex class II molecules (H2-Aa, H2-DMb2, H2-K1, and H2-Q7) and class II invariant chain (CD74), some of which have been reported previously to be regulated by IRF8. 30 It is possible that transcriptional regulators other than KLF4 also play roles downstream of IRF8. For example, IRF8-induced transcription factor genes such as Egr1, Egr2, Maf, and MafB have also been implicated in monocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, IRF8 directly binds to and upregulates multiple genes encoding major histocompatibility complex class II molecules (H2-Aa, H2-DMb2, H2-K1, and H2-Q7) and class II invariant chain (CD74), some of which have been reported previously to be regulated by IRF8. 30 It is possible that transcriptional regulators other than KLF4 also play roles downstream of IRF8. For example, IRF8-induced transcription factor genes such as Egr1, Egr2, Maf, and MafB have also been implicated in monocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous ChIP-on-chip (chromatin immunoprecipitation followed by microarray hybridization) studies of IRF8 have used differentiation-arrested monocytic cell lines or mouse lungs infected with pathogen but not cells undergoing monocytic differentiation. 29,30 It was recently revealed that distal enhancers, characterized by histone H3 lysine 4 monomethylation (H3K4me1), are critical for cell lineage specification. 31 However, the above-mentioned ChIP-on-chip studies examined the regions relatively proximal (27.5 kb to 12.5 kb) to the transcription start sites (TSSs) and did not examine epigenetic changes.…”
Section: Introductionmentioning
confidence: 99%
“…The KLF4-dependent IRF8 target genes are preferentially related to the basic functions of monocytes, such as inflammatory response, chemotaxis, and locomotion, while the KLF4-independent IRF8 target genes are significantly related to more advanced functions, especially antigen presentation. Indeed, IRF8 directly binds to and upregulates multiple genes that encode MHC II and the invariant chain (CD74) [5,26]. Taken together, the evidence indicates that IRF8 cooperates with PU.1 to promote the formation of enhancers to induce various monocyte-related genes, including Klf4, and that the IRF8-KLF4 transcription factor cascade is essential for monocyte development.…”
Section: It Was Initially Thought That Irf8mentioning
confidence: 93%
“…These results confirm that, functionally, sBM-DCs are an IRF8-controlled regDC population. Strikingly, IRF8 was also reported to play a critical role in the regulation of several proinflammatory genes (including IL-12) that function during macrophage activation (53)(54)(55). Whether there is any relationship in IRF8 function between sBM-DC generation and macrophage activation deserves further study.…”
Section: Discussionmentioning
confidence: 99%